First report of microplastic ingestion in lorna (Sciaena deliciosa) off the coast of Huacho, Peru - Romero Bozzetta, Jose Luis (2025)
The aim of this research was to evaluate the presence of microplastics in the digestive contents of lorna (Sciaena deliciosa) in the port of Huacho, Peru. Lorna specimens were collected at four points in the port of Huacho between August and November 2023. Individuals were randomly selected, measured, and weighed. Stomach contents were screened to group microplastics according to size (>0.2, 0.2-0.1, <0.1 mm). No significant differences were found between fish size and weight between the collected groups. The incidence of microplastics in the digestive tract was 10.83% in the individuals evaluated. Besides, 43% of microplastics >0.2 mm was present in the digestive tracts, with a preference for fibre-like and fuchsia-coloured particles. This is the first report of the presence of plastic particles in the gastrointestinal tract of lorna in Huacho, Peru.